Interankle systolic blood pressure difference and renal outcomes in patients with chronic kidney disease. Issue 5 (May 2016) - Chen, Szu‐Chia; Tsai, Yi‐Chun; Huang, Jiun‐Chi; Lee, Su‐Chu; Chang, Jer‐Ming; Hwang, Shang‐Jyh; Chen, Hung‐Chun
Abstract: Aim: Interankle blood pressure (BP) difference has been associated with peripheral artery disease and adverse cardiovascular outcomes. However, the relationship between interankle BP difference and renal outcomes in chronic kidney disease (CKD) has never been evaluated. The purpose of this study was to determine whether interankle BP difference is associated with the rate of renal function decline and progression to renal end points in patients with stage 3–5 CKD. Methods: We enrolled 144 patients with CKD from one regional hospital. The BP in four limbs was simultaneously measured using an ABI‐form device. The decline in renal function was evaluated using an estimated glomerular filtration rate (eGFR) slope. Rapid renal progression was defined as an eGFR slope < −3 mL/min per 1.73 m 2 per year. The renal end points were defined as ≥ 25% decline in eGFR or commencement of dialysis during the follow‐up period. Results: During a mean follow‐up period of 3.1 years, 90 patients (62.5%) reached renal end points. Multivariate analysis showed that an increased interankle systolic BP difference (per 5 mmHg) was associated with a worse eGFR slope (regression β, −0.292; 95% confidence interval [CI], −0.482 to −0.102; P =  0.003), rapid renal progression (odds ratio, 1.189; 95% CI, 1.015–1.394; P =  0.032), and an increased risk of progression to renal end points (hazard ratio, 1.126; 95% CI, 1.052–1.204, P =  0.001). Conclusion: Interankle systolic BP difference was associated with rapid renal progression and progression to renal end points in patients with stage 3–5 CKD in our study. Summary at a Glance: The authors made the novel observation that increased interankle systolic BP difference as a manifestation of peripheral vascular disease was associated with rapid renal progression and progression to renal end points in patients with stage 3–5 CKD. The methodologic ambiguities have been clarified.